Bone Mineral Density and Its Serial Changes Are Associated With PTH Levels in Pseudohypoparathyroidism Type 1B Patients. (3rd January 2018) - Chu, Xueying; Zhu, Yan; Wang, Ou; Nie, Min; Quan, Tingting; Xue, Yu; Wang, Wenbo; Jiang, Yan; Li, Mei; Xia, Weibo; Xing, Xiaoping
ABSTRACT: Bone responsiveness to serum parathyroid hormone (PTH) in pseudohypoparathyroidism 1B (PHP1B) is controversial. Forty‐eight PHP1B patients diagnosed by molecular analysis were recruited from 2000 to 2016 from the Peking Union Medical College Hospital. Fifty‐five sex‐matched nonsurgical hypoparathyroidism (NS‐HP) patients were selected and included for comparison. Basic information, laboratory test, and dual‐energy X‐ray absorptiometry (DXA) results were collected. Linear regression was performed to identify independent predictors of lumbar spine (LS), femoral neck (FN), and total hip (TH) bone mineral density (BMD) Z ‐scores in PHP1B patients. BMD and related markers were compared between PHP and NS‐HP patients. Longitudinal observation of 10 PHP1B patients was performed. The BMD Z ‐score for the LS (1.14 ± 1.41) was higher than that for the FN (–0.20 ± 1.00, p  < 0.001) and the TH (0.03 ± 1.06, p  < 0.001) in PHP1B patients. Despite lower serum calcium levels in untreated patients (1.72 mmol/L in untreated patients versus 2.14 mmol/L in treated patients, p  = 0.024), the PTH levels as well as BMD Z ‐scores were comparable between treated and untreated patients at baseline. PTH was a negative predictor for LS‐BMD Z ‐score ( B  = –0.004, p  = 0.028) for sporadic PHP1B patients, and a similar result was obtained for all the PHP1B patients ( B  = –0.002, p  = 0.053). Z ‐scores for FN‐ and LS‐BMDs after treatment increased by 0.31 ± 0.10 and 0.58 ± 0.12, respectively, where the increase in LS‐BMD correlated with a decrease in PTH ( r  = –0.72, p  = 0.044). All BMD Z ‐scores were significantly lower in PHP1B patients than in IHP patients for the FN, LS, and TH (–0.20 ± 1.00 versus 1.57 ± 1.07, 1.14 ± 1.41 versus 1.96 ± 1.32, 0.03 ± 1.06 versus 1.67 ± 1.01, respectively, all p  < 0.05). Skeletal tissue in PHP1B patients responds to PTH, where heterogenous sensitivities to PTH may exist in different regions of bone. Therefore, it is reasonable to normalize PTH levels when treating PHP1B to avoid negative effects of PTH on bone. © 2017 American Society for Bone and Mineral Research.